Asuhan keperawatan pasien post craniotomy et causa sol intrakranial di intensive care unit: Studi kasus - Tifany, Adinda; Nurhidayah, Irfanita; Fikriyanti, Fikriyanti (Indonesian Journal of Health Science, 2025)
Space Occupying Lesion (SOL) is a critical condition that requires intensive care in monitoring hemodynamic stabilization. SOL refers to a mass or lesion that occupies space within the skull. The pressure from this lesion causes neurological disturbances and increased intracranial pressure (ICP). One of the medical management strategies for SOL patients is craniotomy. This case study aims to describe the nursing care for patients with post-operative craniotomy due to intracranial SOL in the Intensive Care Unit. The methodology used is a case study. The results of this case study show that the diagnoses encountered in the patient include decreased intracranial adaptive capacity, gas exchange disturbances, aspiration risk, infection risk, and ventilator weaning disturbances. The interventions used include intracranial pressure management (ICP), mechanical ventilation management to prevent aspiration, infection prevention, and mechanical ventilation weaning. The conclusion of this case study is that there has been some improvement in the diagnoses, such as gas exchange disturbances and successful ventilator weaning. However, other interventions have not been optimal due to the patient's unstable condition. It is hoped that the patient’s management can be carried out promptly with interventions that support the improvement of the patient’s condition. Space Occupying Lesion (SOL) suatu kondisi kritis yang memerlukan perawatan intensif dalam pemantauan stabilisasi hemodinamik. SOL merupakan massa atau lesi yang mengisi ruang di dalam tengkorak. Pendesakan akibat lesi tersebut mengakibatkan gangguan neurologis dan peningkatan tekanan intrakranial (TIK). Penatalaksanaan medis pasien SOL salah satunya adalah craniotomy. Tujuan dari studi kasus ini adalah untuk mendeskripsikan asuhan keperawatan pada pasien dengan post op craniotomy et causa SOL intrakranial di Intensive Care Unit. Metodologi yang digunakan adalah case study. Hasil studi kasus menunjukkan bahwa diagnosa yang muncul pada pasien yaitu penurunan kapasitas adaptif intrakranial, gangguan pertukaran gas, risiko aspirasi, gangguan penyapihan ventilator, dan risiko infeksi. Intervensi yang digunakan adalah manajemen peningkatan intrakranial (PTIK), manajemen ventilasi mekanik pencegahan aspirasi, penyapihan ventilasi mekanik, dan pencegahan infeksi.  Kesimpulan dari studi kasus ini adalah terdapat sebagaian perbaikan pada diagnosa yaitu gangguan pertukaran gas dan keberhasilan penyapihan ventilator, namun intervensi lainnya belum optimal dikarenakan kondisi pasien yang belum stabil. Diharapkan pelaksanaan penanganan pasien dapat dilakukan segera dengan intervensi yang menunjang perbaikan kondisi pasien.